2014
DOI: 10.1007/s12232-014-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Open issues in happiness research

Abstract: Happiness research is one of the most vivid and fruitful parts of modern economics. The focus is on empirical findings. In contrast, theoretical work has been rather neglected. The paper deals with three areas needing more analytical work: the choice or imposition of comparison or reference groups; and the extent, speed and symmetry of adaptation to positive and negative shocks on happiness. In both areas, theoretical propositions are derived which can in the future be empirically tested. The third area relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…No wonder that a creator of livability theory, Ruut Veenhoven, drives a frugal Volkswagen, and not a luxury Mercedes. For a recent discussion of adaptation and comparison, see Frey et al (2014). (2004) showed that treating it as cardinal in regression does not change results substantially, and therefore, we use OLS.…”
Section: Happinessmentioning
confidence: 99%
See 1 more Smart Citation
“…No wonder that a creator of livability theory, Ruut Veenhoven, drives a frugal Volkswagen, and not a luxury Mercedes. For a recent discussion of adaptation and comparison, see Frey et al (2014). (2004) showed that treating it as cardinal in regression does not change results substantially, and therefore, we use OLS.…”
Section: Happinessmentioning
confidence: 99%
“…As recently lamented by Frey et al (2014), there are many empirical happiness studies, but they do not focus enough on theory. Before we analyze the data for this research, we will briefly discuss broad economic, social, and environmental implications of car use and possible causal pathways from car consumption to happiness.…”
mentioning
confidence: 99%
“…The general literature on well-being has found that socio-economic factors, such as income, education and health, are powerful individual determinants of well-being (see e.g. Shields and Price 2005;Clark et al 2005;Frey, Gallus, and Steiner 2014;Powdthavee and Stutzer 2014). Consequently, demographic groups with relatively low income and education, or relatively poor health, have a lower starting level of well-being than average, making it important to condition the effects of religion on those determinants.…”
Section: Introductionmentioning
confidence: 99%
“…La idea fue retomada por Frey et al (2014) al identificar que los modelos teóricos de la economía de la felicidad necesitan hacer más énfasis en establecer puntualmente cuáles son los grupos de referencia que toman los individuos para autodeterminar sus niveles de bienestar (los niveles de felicidad varían para algunos grupos de referencia, pero no para otros). En Li et al (2014) las ecuaciones basadas en el comportamiento a nivel micro capturan las percepciones sobre el nivel de riesgo en variables medio ambientales, que afectan los niveles de felicidad directamente; entre mayor sea la intensidad en la percepción del riesgo en estas variables, menor será el nivel de felicidad reportado.…”
Section: Modelos Teóricos De Maximización Del Bienestarunclassified